The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1167/iovs.07-1321
|View full text |Cite
|
Sign up to set email alerts
|

A Viscoelastic Biomechanical Model of the Cornea Describing the Effect of Viscosity and Elasticity on Hysteresis

Abstract: A viscoelastic model is presented to illustrate how changing viscosity and elasticity may affect hysteresis. Low hysteresis can be associated with either high elasticity or low elasticity, depending on the viscosity, a finding consistent with clinical reports.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
146
1
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 176 publications
(151 citation statements)
references
References 28 publications
2
146
1
2
Order By: Relevance
“…In this concave state, tear film tension pulls the cornea back toward applanation. 22 The reflection of the infrared light gives indirect evidence that the tear film remains intact in healthy eyes. In this current study we performed ORA measurements on dry-eye patients, but we did not see any difference in the reflection of the infrared light between dry eye and normal subjects.…”
Section: Discussionmentioning
confidence: 99%
“…In this concave state, tear film tension pulls the cornea back toward applanation. 22 The reflection of the infrared light gives indirect evidence that the tear film remains intact in healthy eyes. In this current study we performed ORA measurements on dry-eye patients, but we did not see any difference in the reflection of the infrared light between dry eye and normal subjects.…”
Section: Discussionmentioning
confidence: 99%
“…[26][27][28][29][30] Compared with the number of experimental studies, there is less theoretical work in these aspects. Glass et al 31 developed a simplified model to evaluate the corneal viscosity and elasticity in response to an air puff, but neither the nonlinearity of the corneal elastic properties nor the effect of corneal mass were taken into consideration. Elsheikh et al 32 used finite element analysis to simulate the corneal response as a function of thickness, curvature, age, and true IOP.…”
Section: Discussionmentioning
confidence: 99%
“…They have shown that the cornea has nonlinear viscoelastic behaviour over a large range of pressures (Boyce et al 2007, Glass et al 2008. Nguyen et al have developed a complete nonlinear viscoelastic rheological model for the cornea that considers its anisotropy ).…”
Section: Introductionmentioning
confidence: 99%